Is temporary employment a cause or consequence of poor mental health? - Chris Dawson; Michail Veliziotis; Gail Pacheco; Don Webber (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2014)
Mental health status often has a strong association with labour market outcomes. If people in temporary employment have poorer mental health than those in permanent employment then it is consistent with two mutually inclusive possibilities: temporary employment generates adverse mental health effects and/or individuals with poorer mental health select into temporary from permanent employment. We reveal that permanent workers with poor mental health appear to select into temporary employment thus signalling that prior cross sectional studies may overestimate the influence of employment type on mental health. We also reveal that this selection effect is significantly mitigated by job satisfaction.
Keywords: 330; Employment transitions; Psychological distress; Anxiety; Life satisfaction; Job dissatisfaction